Computer Security - ESORICS 2022 27th European Symposium on Research in Computer Security, Copenhagen, Denmark, September 26-30, 2022, Proceedings, Part I - Atluri, Vijayalakshmi; Di Pietro, Roberto; Jensen, Christian D.; Meng, Weizhi; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
The three volume set LNCS 13554, 13555, 13556 constitutes the proceedings of the 27th European Symposium on Research in Computer Security, ESORICS 2022, which took place in September 2022. The conference took place in Copenhagen, Denmark, in a hybrid mode. The 104 full papers and 6 poster papers presented in these proceedings were carefully reviewed and selected from 562 submissions. They were organized in topical sections as follows: Part I: Blockchain security; privacy; crypto; attacks; sidechannels; Part II: Anonymity; cloud security; access control; authentication; digital signatures; IoT security; applications; Part III: Formal analysis; Web security; hardware security; multiparty computation; ML techniques; cyber-physical systems security; network and software security; posters.
Blockchain Security -- A Blockchain-based Long-Term Time-Stamping Scheme -- Post-Quantum Verifiable Random Function from Symmetric Primitives in PoS Blockchain -- Opportunistic Algorithmic Double-Spending: How I learned to stop worrying and love the Fork -- Zero-History Confidential Chains with Zero-Knowledge Contracts: A New Normal for Decentralized Ledgers -- Secure Hierarchical Deterministic Wallet Supporting Stealth Address -- Zero-Knowledge Age Restriction for GNU Taler -- Privacy -- Privacy Leakage in Privacy-Preserving Neural Network Inference -- Enhancing User Privacy in Mobile Devices Through Prediction of Privacy Preferences -- One vote is enough for analysing privacy -- Local Differential Privacy for Federated Learning -- XSPIR: Effcient Symmetrically Private Information Retrieval from Ring-LWE -- Scaling Up GAEN Pseudorandom Processes: Preparing for a More Extensive Pandemic -- Crypto -- Generic Construction of Trace-and-Revoke Inner Product Functional Encryption -- Spatial Encryption Revisited: From Delegatable Multiple Inner Product Encryption and More -- Public Key Authenticated Encryption with Keyword Search from LWE -- An Effcient Query Recovery Attack Against a Graph Encryption Scheme -- New Unbounded Verifiable Data Streaming for Batch Query with Almost Optimal Overhead -- A Formal Model for Credential Hopping Attacks -- No-directional and Backward-leak Uni-directional Updatable Encryption are Equivalent -- Effcient Circuits for Permuting and Mapping Packed Values Across Leveled Homomorphic Ciphertexts -- Towards Practical Homomorphic Time-Lock Puzzles: Applicability and Verifiability -- Attacks -- Kallima: A Clean-label Framework for Textual Backdoor Attacks -- Two Types of Novel DoS Attacks against CDNs Based on HTTP/2 Flow Control Mechanism -- EVExchange: A Relay Attack on Electric Vehicle Charging System -- Turrin Smart RPKI Validation: Avoiding Errors and Preventing Hijacks -- Cyber Network Resilience against Self-Propagating Malware Attacks -- INC: In-Network Classification of Botnet Propagation at Line Rate -- GAME: Generative-Based Adaptive Model Extraction Attack -- AttacKG: Constructing Technique Knowledge Graph from Cyber Threat Intelligence Reports -- SeInspect: Defending Model Stealing via Heterogeneous Semantic Inspection -- Sidechannels We can hear your PIN drop: A new acoustic side channel attack to profile PIN pads keys -- VAL: Volume and Access Pattern Leakage-abuse Attack with Leaked Documents -- Light the Signal: Optimization of Signal Leakage Attacks against LWE-Based Key Exchange -- BLEWhisperer: Exploiting BLE Advertisements for Data Exfiltration.
Keywords: Data protection; Cryptography; Data encryption (Computer science).; Computer networks -- Security measures; 9; Computer systems; Data and Information Security; Cryptology; Security Services; Mobile and Network Security; Computer Communication Networks; Computer System Implementation